Exploring The Relationship between Intellectual Capital and Firm Value: The Moderating Role of Corporate Governance - Dewi, Sukma; Nazaina, Nazaina; Bensaadi, Iswadi; Faliza, Nur (AIBPM Publisher, 2023)
Every company has a goal to maximize performance. The capital market's supply and demand combine to generate firm value, which is a reflection of the performance of the company. The purpose of this study is to investigate how intellectual capital affects corporate value, and the role of corporate governance as a moderating variable. The population is Food and Beverage companies listed on the IDX 2019-2022. The populations are 21 companies. Sampling obtained census technique. The analysis data uses Moderating Regression Analysis with Eviews. The findings showed that intellectual capital positively and significantly affects corporate value. Firm value is positively and significantly impacted by corporate governance, and corporate governance can moderate the effect of intellectual capital on Firm Value. It is recommended that companies optimize intellectual capital to increase firm value. Investors are advised to consider intellectual capital, and corporate governance that can influence the firm value.Â